2022
DOI: 10.3389/fpubh.2022.1035996
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health risk assessment methods in China: A scoping review

Abstract: BackgroundOver the decades, many assessment methods have been developed around the world and used for occupational health risk assessment (OHRA). This scoping review integrated the literature on methodological studies of OHRA in China and aimed to identifies the research hot-spots and methodological research perspectives on OHRA in China.MethodsA scoping review of literature was undertaken to explore the research progress on OHRA methods in China. Focusing on OHRA methods, the authors systematically searched C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Significant differences in RR among models in 2020 ( Z = 19.21, P < 0.001) and 2021 ( Z = 16.01, P < 0.001) were observed, respectively. It could be observed that the risk levels using the ICMM model could be frequently elevated to very high or intolerable levels, leading to an overestimated evaluation that would exaggerate the real risk points ( 39 ), as indicated in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Significant differences in RR among models in 2020 ( Z = 19.21, P < 0.001) and 2021 ( Z = 16.01, P < 0.001) were observed, respectively. It could be observed that the risk levels using the ICMM model could be frequently elevated to very high or intolerable levels, leading to an overestimated evaluation that would exaggerate the real risk points ( 39 ), as indicated in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The COSHH Essential model, (EPA model) and semi-quantitative risk assessment model (Singapore model and China semi-quantitative risk assessment model) were used to assess occupational health risk of benzene in this study. Each occupational health risk assessment model has its own advantages and disadvantages ( 6 , 7 , 17 ). The COSHH Essential model is mainly used for small and medium-sized enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…Several occupational health risk assessment (OHRA) models have been developed to assess health risks from occupational hazards and provide control measures. OHRA not only estimates the likelihood and extent of hazard occurrence through qualitative or quantitative assessments, but also takes appropriate measures to minimize occupational risks ( 6 ). Currently, the U.S. Environmental Protection Agency (EPA), Singaporean, Australian, Romanian, International Council of Mines and Metals (ICMM) and UK Basic Model for The Control of Hazardous Substances to Health (COSHH) are considered to be the six most common OHRA models, with the Singapore model having good overall compatibility ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of NH occupational poisoning associated with various factors, including long exposure duration, enclosed working environment, poor ventilation or low efficiency of the air circulation system, and insufficient protective measures (4,11). The Occupational Health Risk Assessment (OHRA) model has been proposed as a tool to predict and control the health risks of occupational hazards, which predicts the possibility and extent of hazards by qualitative, quantitative and semiquantitative methods, and proposes corresponding preventive and control measures (12). Currently, the U.S. Environmental Protection Agency (EPA), Singaporean, Australian, Romanian, International Council on Mining and Metals (ICMM), and UK Control of Substances Hazardous to Health (COSHH) Essential models are considered as the six most common OHRA models (13).…”
Section: Introductionmentioning
confidence: 99%